Flower and Fruit Development Phenology and Generative Reproduction Success of Hibiscus rosa-sinensis spp. - Annahwi, Dlohak; Ratnawati, Ratnawati; Budiwati, Budiwati (YRU Journal of Science and Technology, 2018)
Information on flowers and fruits development (phenology) of the species Hibiscus rosa-sinensis spp is needed to support the potential for genetic improvement programs or hybridization, however, is still limited. Thus research on phenology of the flowers and fruits development is important to do. The aims of the research is to investigate the phenological development of flowers and fruits, and generative reproduction success. The design of the research was explorative descriptive with observation method. The study was conducted in the experiment garden of Biology Education Department of UNY. Ten samples of developing flowers taken from one plant were labeled for observation. The observation of developing flowers were done since the very begining of flowering or the initiation phase. Fruit development was observed from the fall of perianth and anther until the fruit maturation. Results show that the average length of flowering period and fruit development is 61 days, with the details as follows: initiation phase is 26 days; preanthesis is 5 days; anthesis is 1 day; pollination and fertilization is 3 days; and fruit development phase is 27 days. Morphologically, the young fruit is green, capsule-shaped, the dimension is 3.2 cm long and 1.3 cm across, the ripe fruit dehisces with many small heart-shaped and brownish-black seeds produced. Moreover, the seed shell is hairy. The generative reproduction success was indicated by the production of viable seeds which are able to germinate and produce offspring showing various morphological juvenile leaves, flowers, and fruits.